THE INFLUENCE OF ACADEMIC PRESSURE, OPPORTUNITY OF CHEATING AND RATIONALIZATION OF CHEATING ON THE BEHAVIOR OF ACADEMIC CHEATING WITH PERCEPTION OF ACCOUNTING ETHICS AS A MODERATING VARIABLE (ON STIE SUTAATMADJA SUBANG ACCOUNTING STUDENTS) - Vina Nur Alviani; Asep Kurniawan; Bambang Sugiharto (JASS (Journal of Accounting for Sustainable Society), 2019)
The purpose of this research is to determine the effect of fraud triangle (academic pressure, opportunity of cheating and rationalization of cheating) to have positive effect on the behavior of academic cheating with the perception of accounting ethics as a moderating variable on STIE Sutaatmadja Subang accounting students. The population in this study were students of accounting department of STIE Sutaatmadja Subang generetions 2014, 2015, 2016 and 2017 as many as 215 students. To determinate the size of the sample using slovin formula and the result is 140 sample students. Sample selection technique using probability sampling while for sampling in this study is using simple random sampling. The dependent variable of behavior of academic cheating. The independent variables are academic pressure, opportunity of cheating and rationalization of cheating. And one moderating variable of perception of accounting ethics. The methods of data analysis is using descriptive statistic and inferential statistic. The result showed that academic pressure had a significant negative effect on behavior toward academic cheating, opportunity of cheating and rationalization of cheating had a significant positive effect on the behavior of academic cheating and the perception of accounting ethics did not moderate academic pressure, opportunity of cheating and rationalization of cheating on behavior of academic cheating.